Pengaruh Profitabilitas, Likuiditas, Leverage Dan Ukuran Perusahaan Terhadap Pengungkapan Corporate Social Responsibility (CSR) Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2021 - Damanik, Anhari Gusvi; Harmain, Hendra; Harahap, Muhammad Ikhsan (Universitas Labuhanbatu, 2023)
This research is to determine the effect of the effect of profitability, liquidity, leverage and company size on corporate social responsibility (CSR) disclosure in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2021. This research uses associative type quantitative research methods and data collection techniques with documentation techniques. The population of this study amounted to 129 main board manufacturing companies listed on the Indonesian stock exchange. The sampling technique used purposive sampling so as to obtain 34 samples. The results of this study indicate that partially Profitability has an effect of 2.241 with a significant level of 0.026 on CSR Disclosure. Then partially Liquidity has no effect of 0.625 with a significant level of 0.532. While Leverage partially has no effect of -0.606 with a significant level of 0.545. And Company Size partially has an effect of 2.652 with a significant level of 0.009. Simultaneously Profitability, Liquidity, Leverage and Company Size affect CSR Disclosure by 3.603 with a significant level of 0.007.